1997
DOI: 10.1051/jp1:1997128
|View full text |Cite
|
Sign up to set email alerts
|

Replica Fourier Tansforms on Ultrametric Trees, and Block-Diagonalizing Multi-Replica Matrices

Abstract: The analysis of objects living on ultrametric trees, in particular the block-diagonalization of 4−replica matrices M αβ;γδ , is shown to be dramatically simplified through the introduction of properly chosen operations on those objects. These are the Replica Fourier Transforms on ultrametric trees. Those transformations are defined and used in the present work. ResuméOn montre que l'analyse d'objets vivant sur un arbre ultrametrique, en particulier, la diagonalisation par blocs d'une matrice M αβ;γδ dependant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 13 publications
(25 reference statements)
2
55
0
7
Order By: Relevance
“…In [21], [22] it was shown that the Parisi matrix describing the replica symmetry breaking (before the n → 0 limit) is a discrete analogue of a p-adic pseudodifferential operator. In [23], [24] the Parisi matrices related to more general Abelian locally compact groups were considered. In [25] the relation of ultrametric diffusion and dynamics of macromolecules was discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In [21], [22] it was shown that the Parisi matrix describing the replica symmetry breaking (before the n → 0 limit) is a discrete analogue of a p-adic pseudodifferential operator. In [23], [24] the Parisi matrices related to more general Abelian locally compact groups were considered. In [25] the relation of ultrametric diffusion and dynamics of macromolecules was discussed.…”
Section: Introductionmentioning
confidence: 99%
“…В [228], [58] обсуждался предел n → 0 метода реплик в p-адической парамет-ризации. В работах Карлуччи, Де Доминичиса, Темесвари [130], [136] обсуждалась связь репличных расчётов и фурье-анализа на абелевых группах. В работах [178], [179], [180] Козырева и Хрен-никова был разработан анзац нарушения репличной симметрии, обобщающий анзац Паризи и связанный с ультраметрическими пространствами общего вида.…”
Section: библиографический обзорunclassified
“…В работах [130], [136] рассматривались матрицы Паризи, свя-занные с локально компактных абелевыми группами, являющи-мися ультраметрическими пространствами. В настоящей главе мы описываем параметризацию также для таких матриц.…”
Section: Introductionunclassified
“…We will present the basic facts on ultrametric spaces, p-adic numbers and p-adic Fourier transform here [32,39,41,42].…”
Section: Appendixmentioning
confidence: 99%